HOW TO UPDATE THE I NTERNAL PUBLIC DEBT FORGOTTEN BY THE GOVERNMENT IN PERU - Avelino Sánchez, Esteban Marino (2014)
How to update the debt of the Bonds for Reconstruc-tion and Development Bonds issued by the Peruvian Government in currencies that were withdrawn from circulation ? Constitutes the problem that this article trying to explain. The operation requires updating previously discerning about the good of economic and the in-dicators for value to be applied in the calculations; in that sense, we propose two methods: Update the US dollar, dollarized debt at the date of issuance of the bonds, plus interest, and updating debt IPC; with which it sums are reasonable; however, expectations fade bondholders reconstruction and development bonds, excited by outsized financial same active low amount of values exposed to hyperinflation; some believe that their purchasing power increased by tens of millions, when in fact hyperinflation has effects opposite direction.